Service denied : marginalized veterans in modern American history - Kinder, John M. (John Matthew), 1975-; Higgins, Jason A., 1985- (Veterans (University of Massachusetts Press), 2022)
"Wartime military service is held up as a marker of civic duty and patriotism, yet the rewards of veteran status have never been equally distributed. Certain groups of military veterans-women, people of color, LGBTQ people, and former service members with stigmatizing conditions, "bad paper" discharges, or criminal records-have been left out of official histories, excised from national consciousness, and denied state recognition and military benefits. Chronicling the untold stories of marginalized veterans in the twentieth and twenty-first centuries, Service Denied uncovers the generational divides, cultural stigmas, and discriminatory policies that affected veterans during and after their military service. Together, the chapters in this collection recast veterans beyond the archetype, inspiring an innovative model for veterans studies that encourages an intersectional and interdisciplinary analysis of veterans history"--